NMDA Receptors: Methods and Protocols - Burnashev, Nail; Szepetowski, Pierre (Methods in molecular biology, 2017)
This volume explores the latest techniques used by researchers to help them better understand the NMDAR structure-function relations, principles, and rules that govern how NMDARs operate in brain processing. The volume includes a detailed introductory chapter describing the field and is divided into three parts. Topics covered in the volume include: quantification of NMDAR subunit genes expression by qRT-PCR; detection of NMDARs antibodies in encephalitis; recombinant channels in host cells using a fast agonist application system; GluNs detection and functions in microglial cells; and NMDARs as voltage sensors. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and practical, NMDA Receptors: Methods and Protocols is a valuable resource that discusses the diversity of the currently-used methods, the importance of NMDARs and their complexity, and the progress that has already been made. This book will be of interest to scientists, clinicians, and industry professionals working in this field.